ASTHMA COURSE IN CHILDREN FROM IODINE DEFICIENT REGION – CLINICAL AND IMMUNOLOGICAL CHARACTERISTIC FEATURES - A.A. Lyagina; N.I. Kosyakova (Педиатрическая фармакология)
The article presents the results of clinical, allergological and immunological examination of 399 children with bronchial asthma, who live in the iodine deficient southern part of Moscow region. The results of dynamic follow up have revealed a prevalence of moderate asthma (47.2%) and a high frequency of severe asthma (11.5%). RELATIVELY SEVERE ASTHMA WAS NOTED IN A Group of children with long term and recurrent respiratory infections and in a group of children with thyroid changes, where the average remission period lasted for 2.3±0.6 and 2.4±0.8 months, respectively (p<0.05). The allergological examination has demonstrated prevalence of household and pollen sensitization. The immunological examination has shown prevailing Th2-immune response. Higher levels of total IgE have been observed in children with more severe asthma when compared to mild moderate (Р<0.05). Higher levels of total IgE and IgG4 have been registered in the group of children with recurrent respiratory infections and in children with thyroid changes.Key words: bronchial asthma, allegrodiagnostics, immunological features, iodine deficiency.